The application of artificial intelligence in economic decision-making and its impact on the labor market - Liu, Chenshuo (Transactions on Economics, Business and Management Research, 2024)
While prospering the economy, artificial intelligence also widely affects the labor market. The exponential growth of production automation poses new challenges to work forms and work demands. Under the social background of the gradual decline of demographic dividend and the gradual decline of personal dividend, the competition for talents and labor among cities has gradually become the focus of Jiaocheng in the new era. Spatial mobility of labor force has become an important topic of regional economic development. AI applications represented by automated production lines, intelligent customer service, driverless cars, intelligent diagnosis systems, etc. have demonstrated the great promotion of technological progress to social productivity. Moreover, most of them focus on the process of introducing artificial intelligence technology to solve some complicated economic operations and data analysis. In the past decades, artificial intelligence has reached or even surpassed the human level in the fields of speech recognition, image recognition and natural language processing, and these technologies have been widely used in various fields.The overall primary product market is in a bull market, which has led to China’s industrial producer ex factory price index being higher than the consumer price index for most years during this period, and the industrial producer purchase price index being higher than the ex factory price index. The application of artificial intelligence in the economic field can promote the rapid development of economic decision-making, strengthen business awareness in the leadership market, and play an important driving role in improving business level.